Improving the phase super-sensitivity of squeezing-assisted interferometers by squeeze factor unbalancing - Manceau, Mathieu; Khalili, Farid; Chekhova, Maria V. (New Journal of Physics, 2017)
The sensitivity properties of an SU(1,1) interferometer made of two cascaded parametric amplifiers, as well as of an ordinary SU(2) interferometer preceded by a squeezer and followed by an anti-squeezer, are theoretically investigated. Several possible experimental configurations are considered, such as the absence or presence of a seed beam, direct or homodyne detection scheme. In all cases we formulate the optimal conditions to achieve phase super-sensitivity, meaning a sensitivity overcoming the shot-noise limit. We show that for a given gain of the first parametric amplifier, unbalancing the interferometer by increasing the gain of the second amplifier improves the interferometer properties. In particular, a broader super-sensitivity phase range and a better overall sensitivity can be achieved by gain unbalancing.
CRIS-Team Scopus Importer:2023-03-27
Keywords: interferometers; phase sensitivity; squeezed state